Pengaruh Ukuran Perusahaan, Operating Capacity, Sales Growth terhadap Financial Distress yang Dimoderasi dengan Profitabilitas - Nancy Dwiyanti; Sri Rahayu (Pajak dan Manajemen Keuangan, 2025)
This research aims to examine the influence of firm size, operating capacity, and sales growth on financial distress, with profitability serving as a moderating variable. The study employs a purposive sampling technique and selects 96 companies from the primary consumer sector listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The data are analyzed using multiple linear regression and Moderated Regression Analysis (MRA) with the assistance of SPSS version 22. The findings reveal that firm size does not have a significant impact on financial distress, indicating that larger firms do not necessarily experience lower financial risk. In contrast, operating capacity and sales growth have a significant and positive influence on financial distress, suggesting that higher capacity utilization and increased sales activities may heighten financial vulnerability. Furthermore, profitability effectively moderates the relationships between firm size, operating capacity, and sales growth with financial distress. This result highlights the vital role of profitability in strengthening a company’s financial stability and mitigating potential financial distress or bankruptcy.